2020
DOI: 10.12688/f1000research.22403.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic options in recurrent implantation failure

Abstract: Recurrent implantation failure (RIF) is an uncommon, imprecisely defined clinical disorder characterized by failure to achieve pregnancy after repeated embryo transfers. The diverse etiologies and incomplete understanding of RIF provide significant diagnostic and therapeutic challenges to patients and providers. Careful clinical evaluation prior to assisted reproduction can uncover many treatable causes, including thyroid dysfunction, submucosal myomas, and tobacco use. The more-subtle causes often require a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 91 publications
0
30
0
2
Order By: Relevance
“…However, despite the increasing trend of the procedure, it has still been facing challenges in terms of a low success rate, which only 10-40% globally [1] and 20-50% locally in Indonesia [2]. Apart from maternal factors, another reason for this sub-optimal outcome is the high number of embryo transfer failures [3], [4], [5]. Failure transfer is related to the insufficient embryo quality to develop reaches pregnancy [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the increasing trend of the procedure, it has still been facing challenges in terms of a low success rate, which only 10-40% globally [1] and 20-50% locally in Indonesia [2]. Apart from maternal factors, another reason for this sub-optimal outcome is the high number of embryo transfer failures [3], [4], [5]. Failure transfer is related to the insufficient embryo quality to develop reaches pregnancy [6].…”
Section: Introductionmentioning
confidence: 99%
“…After a review of the titles and abstracts, 154 studies were identified as potentially eligible for inclusion. After a full review, we excluded 19 systematic reviews or meta-analysis 2,5,22,23,37,[46][47][48][49][50][51][52][53][54][55][56][57][58][59] , 8 case reports [60][61][62][63][64][65][66][67] , 4 letters to the editor [68][69][70][71] and 81 original studies [references and reasons for exclusion are reported in Table 1]. Data on the efficacy of therapies and interventions for RIF were extracted from the remaining 42 articles 8,12,13,18,20,21,24,27,28,31,75, .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, endometriosis was not considered to be a cause of infertility in some of the patients with early-stage endometriosis. In addition, a large number of patients with implantation failure were potentially included in the patients treated with IVF [ 43 , 44 ]. Since it has been reported that CE is related to implantation failure [ 45 , 46 ], and because we hypothesized that the occurrence of EMT was related to implantation failure, IVF patients were targeted in the present study.…”
Section: Discussionmentioning
confidence: 99%